Pharmacoeconomic studies of technologies for prevention of hpv-associated cervical pathologies - S. O. Soloviov; S. I. Zhuk; V. K. Kondratiuk; I. V. Dziublyk; V. V. Trokhymchuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
In Ukraine, cervical cancer (CC) is the second most frequent cancer among women of reproductive age and causes more than two thousand deaths per year. The results of clinical and laboratory studies indicate the high prevalence of human papillomaviruses (HPV) of high carcinogenic risk in Ukraine, being the cause of the development of CC. The concept of pharmaceutical prevention is becoming more and more relevant today as it includes a set of measures aimed at preserving and promoting health, improving the quality of life, preventing the occurrence of pathological conditions and diseases; and if they occur - the progression and worsening of a patient's condition, relapse and transition to chronic form, as well as prevention of possible negative or undesirable consequences. The aim of the work - рharmacoeconomic research using mathematical modeling of prevention technologies of HPV-associated cervical pathologies based on vaccination and diagnostic screening among women of different ages. Pharmacoeconomic analysis of prevention technologies for women aged 18 years and more proposed a developed mathematical model, the overall idea of which reflected the current scientific understanding of the causes and development of CC. The detection of severe dysplasia is the primary purpose of diagnostic screening, and the establishment of diagnostic status in the presence of HPV infection is additional information that allows refining the diagnostic screening scheme. Minimization of total costs implies the simultaneous achievement of the maximum possible socio-economic effect from the introduction of complex technology for the prevention of HPV-associated pathologies of the cervix. It may be seen in the reduction of the total number of undiagnosed persons with severe dysplasia, which will be affected by both HPV vaccination and diagnostic screening. This justification is the basis for formalizing the pharmacoeconomic evaluation of complex technology for the prevention of HPV-associated cervical pathologies in the form of a cost-effectiveness factor. The proposed method of pharmacoeconomic assessment was put into practice using retrospective data of 145 women with a prevalence of young ones aged 22 to 36 years. On the basis of the received frequency, clinical and epidemiological data, it was possible to determine the coefficient of influence of the persistence of HPV on the development of severe forms of dysplasia, as an additional criterion for pharmacoeconomic evaluation. Analytical studies have shown that at constant costs for the diagnosis or vaccination of one person, the cost-effectiveness ratio of complex prevention technology is significantly dependent on the impact of HPV persistence. A case study was examined, in which the cost of diagnostic screening was 10 times lower than the cost of vaccination per person, the HPV vaccination efficiency was 90%, the vaccination coverage rate was 10%, and the non-vaccinated diagnostic screening rate was 80%. In this example, it was shown that the use of HPV persistence as additional weight in the calculation of diagnostic screening coverage allows for more pharmacologically sound prevention regimens due to the lower cost-effectiveness ratio, all else being equal. A method of pharmacoeconomic evaluation based on determining the utility of the costs of diagnostic screening and vaccination for HPV infection as a complex technology for the prevention of HPV-associated cervical pathologies is proposed. An additional criterion for pharmacoeconomic evaluation is the coefficient of the impact of HPV persistence on the development of severe dysplasia, which is equal to the ratio of the proportion of women with severe dysplasia to the proportion of women with HPV at the previous time. Analytical studies have shown that the use of HPV persistence as additional weight in the calculation of diagnostic screening coverage allows for more pharmacologically sound prevention regimens due to the lower cost-effectiveness ratio, all things being equal.